2021
DOI: 10.3390/biomedicines9111722
|View full text |Cite
|
Sign up to set email alerts
|

Obesity-Associated Metabolic Disturbances Reverse the Antioxidant and Anti-Inflammatory Properties of High-Density Lipoproteins in Microglial Cells

Abstract: High-density lipoproteins (HDLs) play an important role in reverse cholesterol transport and present antioxidant properties, among others. In the central nervous system (CNS), there are HDLs, where these lipoproteins could influence brain health. Owing to the new evidence of HDL functionality remodeling in obese patients, and the fact that obesity-associated metabolic disturbances is pro-inflammatory and pro-oxidant, the aim of this study was to investigate if HDL functions are depleted in obese patients and o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 27 publications
0
4
0
Order By: Relevance
“…Furthermore, the high glucose level in obesity is accompanied by insulin resistance and, subsequently, increased neuronal cell loss and BBB permeability, leading to memory loss [ 63 , 64 ]. Another study showed that excessive linoleic polyunsaturated fatty acid is related to hypothalamic inflammation, thus boosting weight gain [ 65 ] and affecting insulin resistance [ 66 ]. In obesity, fatty acid composition is an important factor for predicting the progression of lipid dysregulation and inflammation in obesity.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the high glucose level in obesity is accompanied by insulin resistance and, subsequently, increased neuronal cell loss and BBB permeability, leading to memory loss [ 63 , 64 ]. Another study showed that excessive linoleic polyunsaturated fatty acid is related to hypothalamic inflammation, thus boosting weight gain [ 65 ] and affecting insulin resistance [ 66 ]. In obesity, fatty acid composition is an important factor for predicting the progression of lipid dysregulation and inflammation in obesity.…”
Section: Discussionmentioning
confidence: 99%
“…They have a great potential to be used as a functional ingredient, due to their high nutrition value and good functional properties, e.g. , emulsifying properties, anti-inflammatory, antioxidant, anticancer and antidiabetic activity (Bao et al, 2019 ; Grao-Cruces et al, 2021 ; Tabara et al, 2017 ; Lotfollahi et al, 2021 ). However, their applications were challenged because of poor water solubility, which are mainly attributed to the fact that they have a pseudo-molecular structure close to that of globular proteins and tends to exist in egg yolk granules linked to phosvitin by phosphocalcic bridges (Anton, 2013 ).…”
Section: Introductionmentioning
confidence: 99%
“…It was found that hyperleptinemia led to the increase of oxidized HDL levels [29]. HDLs isolated from normal-weight healthy men (nwHD) induced a reduction in proinflammatory cytokines' production and marker gene expression profile characteristics for the M1 phenotype in microglial cells BV2 [29].…”
mentioning
confidence: 99%
“…It was found that hyperleptinemia led to the increase of oxidized HDL levels [29]. HDLs isolated from normal-weight healthy men (nwHD) induced a reduction in proinflammatory cytokines' production and marker gene expression profile characteristics for the M1 phenotype in microglial cells BV2 [29]. The co-administration of LPS and leptin with nwHDL or HDL isolated from obese men led to the activation of BV2 microglial cells, resulting in the increased production of pro-inflammatory cytokines and proving that obesity led to the reversal of the anti-inflammatory and antioxidant activities of HDLs in a microglial cell model [29].…”
mentioning
confidence: 99%